The Mix of Resources, Security and Sustainability of the Energy Complex in Romania in the European Context - Carmen-Valentina Radulescu; Ioan I. Gaf-Deac; Florina Bran; Catalin-Octavian Manescu; Dumitru Alexandru Bodislav; Sorin Burlacu (Amfiteatru Economic, 2023)
This article presents the results of the research on energy activities in Romania by highlighting the variants of the mix of energy resources, the mix of production alternatives, and ways of energy consumption. The uneven distribution of resource ownership in EU member states is a comparative advantage for Romania, which has significant primary energy resources. The impact of the energy crisis on the new economy is described, and the concept of transitional recession is launched, emphasising the reduction of risks associated with the lack of energy resources in Romania and the EU until 2030. Trends in the production of energy resources are highlighted. The security and environmental problems related to energy consumption under conditions of overlapping crises in the EU and Romania are associated with solutions resulting from the conceptualisation of the adaptive energy market. Aspects of managerial applications in the field of predictable/unpredictable events in the field of energy in Romania are reported. Therefore, the foundations are laid for a formalisation model of the security and safety conditions and the premises for the independence of Romania's energy. On this basis, the maximisation of the output of the security and safety states model is pursued and the premises for Romania's energy independence, respectively, the minimisation of environmental effects, are systematised. Based on the calculations and evaluations of three scenarios, a variant of the electricity/energy production mix results that meets the objectives pursued. In fact, a block scheme of approach is proposed, from the vision to the roadmap for the energy field in Romania, the idea of open energy autonomy being launched, considered appropriate with the ecoeconomic, productive-industrial behaviour of Romania.
Keywords: C67; D24; E27; L72; 330; Security; mix of energy resources; adaptive energy market; open energy autonomy